Document analysis and recognition : 4th Workshop, DAR 2018, held in Conjunction with ICVGIP 2018, Hyderabad, India, December 18, 2018, Revised Selected Papers /: 4th Workshop, DAR 2018, held in Conjunction with ICVGIP 2018, Hyderabad, India, December 18, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available